The impact of the Public Pension Program on the elderly's medical expenditures: a regression discontinuity approach. Issue 1 (31st December 2022) - Si, Xu; Chu, Fu-Ling
ABSTRACT: The surge in aging societies has increased the relevance of retirement as a research topic. Utilizing the public data obtained from the China Family Panel Studies, this paper applies a regression discontinuity approach to assess the impact of China's current Public Pension Program on the medical expenditures of the elderly. The results reveal that the Public Pension Program increases out-of-pocket medical expenditures, hospitalization expenditures, and other injury and illness expenses. The results also report that being insured by Basic Social Health Insurance has a mitigating effect on the medical expenditures of the elderly; furthermore, there are significant differences in the use of medical resources between regions and urban and rural areas in China. Therefore, ensuring the sustainability of pension funds and social health insurance funds and developing customized private insurance according to areas can play a positive role in improving the use of medical resources and relieving the medical burden on the elderly population.